2022
DOI: 10.1155/2022/2333848
|View full text |Cite
|
Sign up to set email alerts
|

HSPA12A Stimulates p38/ERK-AP-1 Signaling to Promote Angiogenesis and Is Required for Functional Recovery Postmyocardial Infarction

Abstract: Angiogenesis plays a critical role in wound healing postmyocardial infarction (MI). However, there is still a lack of ideal angiogenic therapeutics for rescuing ischemic hearts clinically, suggesting that a more understanding regarding angiogenesis regulation is urgently needed. Heat shock protein A12A (HSPA12A) is an atypical member of the HSP70 family. Here, we demonstrated that HSPA12A was upregulated during endothelial tube formation, a characteristic of in vitro angiogenesis. Intriguingly, overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Heat shock protein 12A (HSPA12A) is a novel activator of angiogenesis that increases the expression of VEGF and the phosphorylation level of ERK in ECs, thereby mediating angiogenesis ( Dai et al, 2021 ). The ERK inhibitor PD98059 attenuates the phosphorylation of VEGF and VEGFR2 expression through HSPA12A and attenuates angiogenic features in vitro ; knockdown of HSPA12A in mice impairs cardiac angiogenesis after myocardial infarction and exacerbates cardiac dysfunction ( Li et al, 2022 ). Studies have shown that hypoxic factors activate the ERK signaling pathway and HIF-1α participates in the regulation mechanism of the ERK signaling pathway ( Zhang Q. et al, 2014 ).…”
Section: The Role Of the Erk Signaling Pathway In Ischemic Diseases T...mentioning
confidence: 99%
“…Heat shock protein 12A (HSPA12A) is a novel activator of angiogenesis that increases the expression of VEGF and the phosphorylation level of ERK in ECs, thereby mediating angiogenesis ( Dai et al, 2021 ). The ERK inhibitor PD98059 attenuates the phosphorylation of VEGF and VEGFR2 expression through HSPA12A and attenuates angiogenic features in vitro ; knockdown of HSPA12A in mice impairs cardiac angiogenesis after myocardial infarction and exacerbates cardiac dysfunction ( Li et al, 2022 ). Studies have shown that hypoxic factors activate the ERK signaling pathway and HIF-1α participates in the regulation mechanism of the ERK signaling pathway ( Zhang Q. et al, 2014 ).…”
Section: The Role Of the Erk Signaling Pathway In Ischemic Diseases T...mentioning
confidence: 99%
“…Heat-shock protein A12A (HSPA12A), an atypical member of the heat-shock protein 70 family, is initially identified in 2003, and the subsequent research reveals a high level of HSPA12A in the human and murine brains under normal circumstances, but a reduced expression of HSPA12A in the prefrontal cortex of patients with schizophrenia (Han et al, 2003;Pongrac et al, 2004). Recently, the aberrantly downregulated expression of HSPA12A has been involved in multiple disorders, including obesity, nonalcoholic steatohepatitis, and myocardial infarction, and HSPA12A may represent a broad-spectrum strategy for the management of different diseases (Kong et al, 2019;Li et al, 2022;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Heat‐shock protein A12A (HSPA12A), an atypical member of the heat‐shock protein 70 family, is initially identified in 2003, and the subsequent research reveals a high level of HSPA12A in the human and murine brains under normal circumstances, but a reduced expression of HSPA12A in the prefrontal cortex of patients with schizophrenia (Han et al, 2003; Pongrac et al, 2004). Recently, the aberrantly downregulated expression of HSPA12A has been involved in multiple disorders, including obesity, nonalcoholic steatohepatitis, and myocardial infarction, and HSPA12A may represent a broad‐spectrum strategy for the management of different diseases (Kong et al, 2019; Li et al, 2022; Zhang et al, 2019). Of particular interest, HSPA12A encodes a crucial pro‐survival pathway during ischemic stroke as HSPA12A deficiency aggravates ischemic brain injury, including neuronal deficits, hippocampal damage, and motor function impairment, suggesting HSPA12A as a novel neuroprotective target for the treatment of ischemic stroke (Mao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Te survival or programmed cell death of human microvascular endothelial cells is strongly infuenced by MAPK pathway activation [14]. In this family, stressactivated protein kinase 2 (p38), C-Jun NH2-terminal kinase (JNK), and extracellular signal-regulated kinase (ERK) pathways are associated with signal transduction in angiogenesis [15][16][17]. MAPK family members are phosphorylated by cascade regulation and activated by extracellular stimulation [18], and studies have shown that this pathway assists in developing DR [19,20].…”
Section: Introductionmentioning
confidence: 99%